Synthesis of silver nanoparticles using plants extract and analysis of their antimicrobial property - Logeswari, Peter; Silambarasan, Sivagnanam; Abraham, Jayanthi (Journal of Saudi Chemical Society, 2015)
Plants extract from Ocimum tenuiflorum, Solanum tricobatum, Syzygium cumini, Centella asiatica and Citrus sinensis was used for the synthesis of silver nanoparticles (Ag NPs) from silver nitrate solution. Ag NPs were characterized by UV–vis spectrophotometer, X-ray diffractometer (XRD), atomic force microscope (AFM) and scanning electron microscope (SEM). The formation and stability of the reduced silver nanoparticles in the colloidal solution were monitored by UV–vis spectrophotometer analysis. The mean particle diameter of silver nanoparticles was calculated from the XRD pattern according to the line width of the plane, refraction peak using the Scherrer’s equation. AFM showed the formation of silver nanoparticle with an average size of 28 nm, 26.5 nm, 65 nm, 22.3 nm and 28.4 nm corresponding to O. tenuiflorum, S. cumini, C. sinensis, S. tricobatum and C. asiatica, respectively. SEM determination of the brown color stable samples showed the formation of silver nanoparticles and well dispersed nanoparticles could be seen in the samples treated with silver nitrate. Antimicrobial activity of the silver bio-nanoparticles was performed by well diffusion method against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumoniae. The highest antimicrobial activity of silver nanoparticles synthesized by S. tricobatum, O. tenuiflorum extracts was found against S. aureus (30 mm) and E. coli (30 mm) respectively. The Ag NPs synthesized in this process has the efficient antimicrobial activity against pathogenic bacteria. Of these, silver nanoparticles are playing a major role in the field of nanotechnology and nanomedicine.